Digital systems design with FPGAs and CPLDs. - Grout, Ian, ....- (Amsterdam : Elsevier, 2008)
Table of Contents Chapter 1 Introduction to Programmable Logic Chapter 2 Electronic Systems Design Chapter 3 PCB Design Chapter 4 Design Languages Chapter 5 Introduction to Digital Logic Design (Design Principles) Chapter 6 Introduction to Digital Logic Design with VHDL Chapter 7 Introduction to Digital Signal Processing Chapter 8 Interfacing Digital Logic to the "Real World": A/D Conversion, D/A Conversion and Power Electronics Chapter 9 Testing the Electronic System Chapter 10 Systems Level Design Appendix A Organisations and Standards Appendix B Programmable Logic Device Vendors Appendix C Integrated Circuit Package Types Appendix D Modelling and Simulation Language Summary Appendix E Introduction to the Design Tools Appendix F Case Study PCB Designs Appendix G Chapter 6 VHDL Code Examples Appendix H Chapter 7 VHDL Code Examples Appendix I Chapter 8 VHDL Code Examples Appendix J Chapter 10 Code Examples Bibliography